ANALISIS PREFERENSI PELANGGAN GENERASI MILENIAL DAN GENERASI Z TERHADAP DEKORASI PERNIKAHAN TAHUN 2024 - Nandhika, Alsya Dewi; Mustikasari, Ati (Department of Management - Institut Shanti Bhuana, 2024)
Wedding decorations influence guests' perception of wedding memories. Millennials and Generation Z creatively personalize weddings to reflect their unique personalities and values. Wedding service providers, such as Sari Anzailla Wedding Package, need an in-depth understanding of the evolving décor preferences of generations in relation to product attributes. This research aims to provide insights into the wedding decoration preferences of Millennials and Generation Z. The data collection technique in this study used a questionnaire to 88 Sari Anzailla Wedding Package customers. The data obtained was processed using Conjoin Analysis. The product attributes in this study are price, color, design, shape, and style. The research findings show that price is the highest attribute at 34.026% and shape is the lowest attribute with a value of 9.900%. This indicates that price is the main preference of both generations regarding wedding decoration preferences. Sari Anzailla Wedding Package can use the knowledge of the five attributes that have been explored to help build wedding décor offerings and services that suit the tastes of its target customers who are mostly made up of Millennials and Generation Z.